International Approaches to Rape - Gangoli, Geetanjali; Westmarland, Nicole (Policy Press, 2011)
By introducing readers to national perspectives of issues relating to rape, the book presents a comparative approach which highlights similarities and differences between countries, contexts, laws, key issues and policies and interventions.